Share
Explore BrainMass

Gradient: two scalar point functions

Important Formulas and their Explanations (II):
Gradient, Divergence and Curl
Gradient of the differnece of two scalar point functions.

Gradient of the difference of two scalar point functions

If f and g are two scalar point functions, then prove that
grad ( f - g ) = grad f - grad g
that is, ( f - g ) = f - g

that is, gradient of ( f - g ) = gradient of f - gradient of g

Solution Summary

Gradient of the difference of two scalar point functions

If f and g are two scalar point functions, then prove that
grad ( f - g ) = grad f - grad g
that is, ( f - g ) = f - g

that is, gradient of ( f - g ) = gradient of f - gradient of g

Solution contains detailed step-by-step explanation.

$2.19